1996
DOI: 10.1143/jjap.35.4302
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TB(S)CCO Superconductor Coating by Electrophoretic Deposition Method

Abstract: The preparation of Tl2Ba2Ca2Cu3O10+ x (TBCCO) superconducting oxide coating on Ag wire by the electrophoretic deposition method was investigated. Because it was the TBCCO powder is chemically stable in cyclohexanone, and a cyclohexanone bath (20 m l cyclohexanone+2.0 mg iodine+0.4 g TBCCO powder) was used. The deposited sample dried by hot air was sintered at 785° C for 10 min in Tl atmosphere, and T c,zero was 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…4) The negative group velocity of an essentially one-dimensional wave has been observed in the Lamb wave excited in multilayered structures. 5,6) Negative refraction results in a ''lens effect'' without convex or parabolic shape. In other words, a flat acoustic lens can be designed using phononic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…4) The negative group velocity of an essentially one-dimensional wave has been observed in the Lamb wave excited in multilayered structures. 5,6) Negative refraction results in a ''lens effect'' without convex or parabolic shape. In other words, a flat acoustic lens can be designed using phononic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] In 1996, Negishi and Li visualized the third-order anti-symmetric backward mode (A 3b ) excited by an ultrasonic pulse in water obliquely striking the glass plate using photoelastic technique, and claimed that the wavelength of S 2b mode will become too large to be observed. [13] However, according to our numerical calculation and experimental results, it can be demonstrated that the leakage of acoustic energy for S 2b mode is more rapid than that of A 3b mode when the plate is immersed in water. As a result, S 2b mode can only be detected during a very short time.…”
mentioning
confidence: 65%
“…It can be obtained that the main reason for the failure to visualize S 2b mode in Ref. [13] is the energy leakage instead of large wavelength. To explore the propagation characteristics of backward waves in detail, the plate was placed in air to avoid energy leakage in the following experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the negative group velocities appear near cut-off frequencies of particular propagation modes. 9) The range of the existing negative group velocities was found to depend on Poisson's ratio. 10) Indeed, the propagation characteristics of Lamb waves depend on the parameters of each material; therefore, the controllable range of the negative group velocities of the Lamb waves is quite limited.…”
Section: Introductionmentioning
confidence: 95%